Synthesis and Characterization of Biodegradable Plastics from Areca Nut Shell Cellulose Incorporated Carboxymethyl Cellulose (CMC) and Glycerol - Medyan Riza; Tezara Cionita; Rozanna Dewi; Aldila Ananda; Novi Sylvia; Januar Parlaungan Siregar (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
Areca nut shells have a high cellulose content. The potential utilization of areca nut shells as a base material for biodegradable plastics is a key component in the goal of replacing commercial plastics. This study aims to determine the optimal concentration of CMC and glycerol to achieve the best mechanical characteristics of biodegradable plastics. The research method consists of several stages, including the preparation of cellulose from areca nut shells, which involves predelignification and delignification, the synthesis of biodegradable plastic, and the testing of the resulting biodegradable plastic. The mechanical characteristic tests conducted on biodegradable plastics included a tensile strength test (1.27−3.10 MPa), elongation (1.10−1.25%), and Young’s modulus (108.54−281.81 MPa) on biodegradable plastics with CMC (4, 5, 6, and 7%) and 4.5% glycerol. In the functional group analysis, biodegradable plastic forms clusters that bond with water, making soil degradation easier. In the thermal analysis, the most significant weight loss occurred between 422.21°C and 492.87°C, which is the stage of cellulose degradation. The swelling value obtained in the areca nut shell cellulose biodegradable plastic is (25.39-11.17%). The use of glycerol affects the value of plastic resistance to water. Estimated degradation times were 45–63 days (3% glycerol), 81–96 days (3.5%), 75–90 days (4%), and 69–84 days (4.5%). Based on ASTM D6400 standards, the material demonstrates biodegradability, with the potential to meet the required degradation thresholds for bioplastics.